2020
DOI: 10.21203/rs.3.rs-96290/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated With Involuntary Psychiatric Hospitalization in Portugal

Abstract: BackgroundIdentifying which factors contribute to involuntary psychiatric hospitalization may support initiatives to reduce its frequency. This study examines the sociodemographic, clinical, and contextual factors associated with involuntary hospitalization of patients from five Portuguese psychiatric departments in 2002, 2007 and 2012.MethodsData from all admissions were extracted from clinical files. A Poisson generalized linear model estimated the association between the number of involuntary hospitalizatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…These variables were associated with the need for a high-acuity unit in the linear regression analysis. Previous studies pointed out that severe symptoms are associated with high utilization of emergency services (9,13,24). To secure the lives of and benefits to such patients, intensive 24-hour care and equipment specific to psychiatric emergencies based on sufficient staff and a high standard of medical care in a high-acuity unit appear to be needed (1,2,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables were associated with the need for a high-acuity unit in the linear regression analysis. Previous studies pointed out that severe symptoms are associated with high utilization of emergency services (9,13,24). To secure the lives of and benefits to such patients, intensive 24-hour care and equipment specific to psychiatric emergencies based on sufficient staff and a high standard of medical care in a high-acuity unit appear to be needed (1,2,15).…”
Section: Discussionmentioning
confidence: 99%
“…The common diagnoses of acute psychiatric inpatients were schizophrenia and dementia (10,11). Other studies have reported that patients with involuntary admission, which represents the majority of admissions to acute psychiatric units, are characterized by the presence of psychosis and a high number of various clinical problems (13). Three qualitative studies examined clinical profiles of patients admitted to acute units in more detail (8,14,15).…”
Section: Introductionmentioning
confidence: 99%